Effective Charge Influence on Form Factors Calculations of Some Sn Isotopes (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
The longitudinal form factors of 102,104,106Sn nuclei were calculated for two cases: with and without the core polarization effects. In this study, different values of effective charge were used to calculate the longitudinal form factors. e_p=1.5e,e_n=0.88e,e_p=0.98e,e_n=0.88e ,e_p=0.5e ,e_n=0.4e and e_p=0.35e ,e_n=0.35e and are plotted using black, blue, red and green curves, respectively, in all figures. The form factors of isotopes were also studied within shell model, using 100Sn as the inert core, and the others particles distributed on (1H9/2, 2F7/2, 2F5/2, 3P3/2, 3P1/2, and 1I13/2), which constitute the model space. The calculations in this study are based on a harmonic oscillator potential with a constant magnitude parameter (b) using the first-order correction of the Cohen-Korath (CK) perturbation and interaction theory. The inclusion of core polarization effect enhances the diffraction pattern of longitudinal form factors and it has the similar behavior for all different values of effective charge.